EFFECT OF CROSSWORD PUZZLE TEACHING STRATEGY TOWARDS STUDENTS’ VOCABULARY MASTERY - Friska Novi Silalahi; Vivin Sunarko; Nani Haro; Sri Ninta Tarigan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This research is to find out that crossword puzzle teaching strategy gives a significant effect towards students’ vocabulary mastery at SMA Amir Hamzah Medan. The crossword puzzle is a kind of word game which can improve the learners to enrich their vocabulary knowledge. The research design used is pre-experimental design formed as one group pretest- posttest design using quantitative approach. The data collecting method is test. The research data are analyzed by applying paired samples t-test formula through SPSS 23 and the result of the research shows that the value of the t-count is 51,700, while the t-table with the significance level of 5% and Df of 12 is 2,179. The t-count is higher than the t-table (51,7002,179). This  means that the null hypothesis (H0) is rejected while the alternative hypothesis (Ha) is accepted. In conclusion, there is a significant effect towards students’ vocabulary mastery before and after having taught by the utilization of crossword puzzle teaching strategy at SMA Amir Hamzah Medan.